Effective Leadership and Social Entrepreneurship Engagement in Optimal MSMEs Performance - Aryan Torrido (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
This study explores the synergistic relationship between effective leadership and social entrepreneurship engagement as key drivers for optimizing the performance of Micro, Small, and Medium Enterprises (MSMEs). As MSMEs play a pivotal role in fostering economic growth and societal well-being, understanding the nuanced dynamics that contribute to their success is paramount. The research delves into the multifaceted dimensions of effective leadership, encompassing transformative, servant, and inclusive leadership styles. It investigates how these leadership approaches influence organizational culture, employee motivation, and innovation within MSMEs. Moreover, the study examines the impact of social entrepreneurship engagement on MSMEs, emphasizing the integration of social and environmental responsibility into business practices. By employing a mixed-methods research design, including surveys, interviews, and case studies, the study aims to provide a comprehensive analysis of the interplay between leadership effectiveness, social entrepreneurship, and MSMEs performance. Preliminary findings suggest that organizations led by leaders who embrace adaptive and socially conscious strategies demonstrate increased resilience, employee satisfaction, and community engagement. The research contributes to both academic and practical perspectives by offering actionable insights for policymakers, business leaders, and entrepreneurs seeking to enhance MSMEs' contributions to sustainable development. The findings highlight the importance of cultivating leadership skills that prioritize ethical decision-making, stakeholder collaboration, and social impact.